Alleviation of water stress in roselle (Hibiscus sabdariffa L.) using zeolite - Nisa, Mehar Un (2018)
Water stress is one of the major limiting factors for plant growth and yield. Water stress affects plants by imposing numerous morphological, physiological and molecular changes. There are various approaches for mitigation of plant under water stress. One of the approaches is through the zeolite application by improving growth, physiological and biochemical attributes. The response of roselle plant variety UMKL-1 subjected to different soil moisture content (100%, 67% and 33% FC) was investigated under rain shelter. The objective of this study was to determine the effects of different soil moisture content on growth performance and physiological changes, calyx yield and quality in H. sabdariffa. Severe water stress (33% FC) significantly decreased dry matter production, harvest index and photosynthetic rate due to limitation in the efficiency of assimilate translocation. LWP, relative growth rate and nutrient content (N, P, and K) in H. sabdariffa was also significantly decreased at 33 % FC. Root to shoot ratio, accumulation of proline were increased when plants at 33 % FC. The changes in the number of branches and chlorophyll content were not significant. Moreover, H. sabdariffa calyx yield was not significantly different at 100 % and 67 % FC. On the other hand, higher content of total soluble solids, ascorbic acid and anthocyanin were observed at 33% FC. In the 2nd experiment, zeolite used to minimize the adverse effects of water stress on growth, and calyx yield under rain shelter condition. Zeolite application improved growth and yield due to improved dry matter production, nutrient content (N, P, and K) stomatal conductance and photosynthetic rate. Quantitative gene expression studies indicate that the expression pattern of P5CS gene was up-regulated and PDH gene was down-regulated at 33% FC as compared to 67% FC. When zeolite was applied under water stress conditions, the expression pattern of P5CS gene was down-regulated and PDH gene was up-regulated. These results suggested that severe water stress (33% FC) had negative effects on H. sabdariffa yield by reducing growth, photosynthetic rate and nutrient uptake. Zeolite application can be useful to save water that leads more yield under water stress conditions. 67 % FC with 2.50 g zeolite kg−1 soil was found to be more effective in improving growth and calyx yield. This study also established and validated Actin-7 and alpha tubulin-4 as the reference genes in H. sabdariffa under water stress conditions and provides a powerful tool for the quantitative expression analysis of P5CS and PDH in H. sabdariffa. Furthermore, P5CS could participate in the drought resistance process by regulating proline content in H. sabdariffa leaves.